Effects of geometry in the operation of coaxial electrosprays. (January 2023) - López-Herrera, J.M.; Herrada, M.A.; Gamero-Castaño, M.; Gañán-Calvo, A.M.
Abstract: Coaxial electrospray is a well established procedure to generate coaxial micro- and nano-structures (microcapsules and coaxial fibers). In this work we show the capabilities of a high-precision numerical code using dynamic mapping, analytic Jacobian formulation and the Taylor–Melcher leaky dielectric model (LDM) to deal with real coaxial electrospray configurations. Since the number of parameters involved in the problem is large, we focus on an experimentally tested liquid pair configuration where the thickness, relative position, and end sharpness of the coaxial feeding tubes are geometrical parameters of interest. The effects of those parameters and the voltage applied at the tubes on the coaxial liquid menisci, liquid streamlines, size of jet and core, and electric current are discussed. Highlights: The influence of the outlet tube geometry on coaxial electrosprays is studied. Accurate numerical solutions are given using Taylor–Melcher Leaky Dielectric model Protruding, flush and recessed tube outlet setups, and edge sharpening are explored Physical details (streamline patterns, menisci geometries, stresses) are provided